Radiation tolerance studies of silicon microstrip sensors for the CBM Silicon Tracking System. (January 2016) - Momot, I.; Singla, M.; Teklishyn, M.; Pugatch, V.; Heuser, J.
Abstract: Double-sided silicon microstrip sensors will be used in the Silicon Tracking System of the CBM experiment. During experimental run they will be exposed to a radiation field of up to 1x10 14 1 MeV n eq cm -2 . Radiation tolerance studies were made on prototypes from two different vendors. Results from these prototype detectors before and after irradiation to twice that neutron fluence are discussed.